In Situ Formation of Carbon Nanomaterials on Bulk Metallic Materials. (11th March 2014) - Xu, J. Y.; Lei, X. C.; Yang, R.; Fan, Z. Z.
Abstract : Carbon nanomaterials were synthesized in situ on bulk 316L stainless steel, pure cobalt, and pure nickel by hybrid surface mechanical attrition treatment (SMAT). The microstructures of the treated samples and the resulted carbon nanomaterials were investigated by SEM and TEM characterizations. Different substrates resulted in different morphologies of products. The diameter of carbon nanomaterials is related to the size of the nanograins on the surface layer of substrates. The possible growth mechanism was discussed. Effects of the main parameters of the synthesis, including the carbon source and gas reactant composition, hydrogen, and the reaction temperature, were studied. Using hybrid SMAT is proved to be an effective way to synthesize carbon nanomaterials in situ on surfaces of metallic materials.